A randomized controlled trial of hospital versus home based therapy with oral amoxicillin for severe pneumonia in children aged 3 – 59 months: The IndiaCLEN Severe Pneumonia Oral Therapy (ISPOT) Study. Issue 1 (December 2015) - Patel, Archana; Bang, Akash; Singh, Meenu; Dhande, Leena; Chelliah, Luke; Malik, Ashraf; Khadse, Sandhya
Abstract Background Pneumonia is the leading cause of child mortality under five years of age worldwide. For pneumonia with chest indrawing in children aged 3–59 months, injectable penicillin and hospitalization was the recommended treatment. This increased the health care cost and exposure to nosocomial infections. We compared the clinical and cost outcomes of a seven day treatment with oral amoxicillin with the first 48 h of treatment given in the hospital (hospital group) or at home (home group). Methods We conducted an open-label, multi-center, two-arm randomized clinical trial at six tertiary hospitals in India. Children aged 3 to 59 months with chest indrawing pneumonia were randomized to home or hospital group. Clinical outcomes, treatment adherence, and patient safety were monitored through home visits on day 3, 5, 8, and 14 with an additional visit for the home group at 24 h. Clinical outcomes included treatment failure rates up to 7 days (primary outcome) and between 8–14 days (secondary outcome) using the intention to treat and per protocol analyses. Cost outcomes included direct medical, direct non-medical and indirect costs for a random 17 % subsample using the micro-costing technique. Results 1118 children were enrolled and randomized to home (n = 554) or hospital group (n = 564). Both groups had similar baseline characteristics. Overall treatment failure rate was 11.5 % (per protocol analysis). The hospital group was significantly more likely to fail treatment than the home group in the intention to treat analysis. Predictors with increased risk of treatment failure at any time were age 3–11 months, receiving antibiotics within 48 h prior to enrolment and use of high polluting fuel. Death rates at 7 or 14 days did not differ significantly. (Difference −0.0 %; 95 % CI −0.5 to 0.5). The median total treatment cost was Rs. 399 for the home group versus Rs. 602 for the hospital group (p < 0.001), for the same effect of 5 % failure rate at the end of 7 days of treatment in the random subsample. Conclusions Home based oral amoxicillin treatment was equivalent to hospital treatment for first 48 h in selected children of chest indrawing pneumonia and was cheaper. Consistent with the recent WHO simplified guidelines, management with home based oral amoxicillin for select children with only fast breathing and chest-indrawing can be a cost effective intervention. Trial Registration ClinicalTrials.govNCT01386840, registered 25th June 2011 and the Indian Council of Medical Research REFCTRI/2010/000629.